Improving triage for children with comorbidity using the ED-PEWS: an observational study. Issue 3 (21st July 2021) - Zachariasse, Joany M; Espina, Pinky Rose; Borensztajn, Dorine M; Nieboer, Daan; Maconochie, Ian K; Steyerberg, Ewout W; van der Lei, Johan; Greber-Platzer, Susanne; Moll, Henriette A
Abstract : Objective: To assess the value of the Emergency Department–Pediatric Early Warning Score (ED-PEWS) for triage of children with comorbidity. Design: Secondary analysis of a prospective cohort. Setting and patients: 53 829 consecutive ED visits of children <16 years in three European hospitals (Netherlands, UK and Austria) participating in the TrIAGE (Triage Improvements Across General Emergency departments) project in different periods (2012–2015). Intervention: ED-PEWS, a score consisting of age and six physiological parameters. Main outcome measure: A three-category reference standard as proxy for true patient urgency. We assessed discrimination and calibration of the ED-PEWS for children with comorbidity (complex and non-complex) and without comorbidity. In addition, we evaluated the value of adding the ED-PEWS to the routinely used Manchester Triage System (MTS). Results: 5053 (9%) children had underlying non-complex morbidity and 5537 (10%) had complex comorbidity. The c-statistic for identification of high-urgency patients was 0.86 (95% prediction interval 0.84–0.88) for children without comorbidity, 0.87 (0.82–0.92) for non-complex and 0.86 (0.84–0.88) for complex comorbidity. For high and intermediate urgency, the c-statistic was 0.63 (0.62–0.63), 0.63 (0.61–0.65) and 0.63 (0.55–0.73) respectively. Sensitivity was slightly higher for children with comorbidity (0.73–0.75 vs 0.70) at the cost of a lower specificity (0.86–0.87 vs 0.92). Calibration was largely similar. Adding the ED-PEWS to the MTS for children with comorbidity improved performance, except in the setting with few high-urgency patients. Conclusions: The ED-PEWS has a similar performance in children with and without comorbidity. Adding the ED-PEWS to the MTS for children with comorbidity improves triage, except in the setting with few high-urgency patients. Abstract : Through a secondary analysis, the authors assessed the value of the ED-Pediatric Early Warning Score (ED-PEWS) for triage of children with comorbidity. They found that ED-PEWS has a similar performance in children with and without comorbidity and improved triage in most cases.